THE MUSLIM SHOW: SOFT CONTRA "LABELING" MELALUI MEDIA SOSIAL - Yuliana Rakhmawati (Jurnal Komunikasi, 2015)
Post-event 911 Muslims get “labeling” as an entity that refers  to  the  fatalist devian, fundamentalists, terrorists and a number of other negative Labeling. Labeling (labeling) can not be separated from the role  of the  mass media to distribute messages containing the theme of  labeling. An  idea promoted by some Western media tend to provide reinforcement on the labeling. As one of the sensitive issues that tendentious depiction of Islam and labeling will be a provocative theme.Most Muslims respond to such labeling in ways counterproductive. However, most respond with high context communication through the dissemination of messages clarification by using social media. One such action is through the production and distribution of the comic «The Muslim Show» (TMS). Visualization packaging and design of messages in the TMS showed the creativity of the author to show the entity- whether Muslims specifically or so on about the condition of multidimensional community of Muslims. The themes in the comic duo made by the French Muslims are trying to show the positive side, peaceful Islam in the fight against Islamophobia.